Transformative Practices in Archaeology
XXVII, 343 p. 130 illus., 114 illus. in color.
Keywords: The volume introduces a diverse range of themes and practices relating to sustainable heritage management. Each paper delves into the challenges, successes, and failures of preserving precious cultural heritage. It discusses various strategies, such as the early inclusion of archaeology in UNESCO frameworks to leveraging archaeological findings and indigenous knowledge for sustainable development goals. The chapters explore the evolution of autoarchaeology as a tool for empowering Indigenous communities to assert their human rights and integrating oral histories and local ecological knowledge to interpret ancient remains. Additionally, it highlights the value of archaeologists working more closely with Indigenous peoples, local communities, and other disciplines in identifying, preserving, conserving and managing heritage sites. It appeals to archaeologists, anthropologists, cultural geographers, cultural heritage professionals and others seeking new ways to protect cultural heritage.